Fabrication, Characterization, and Application of Clay-Based Ceramic Membranes for Oily Wastewater Treatment: A Review - Mu’azu ABUBAKAR; Abubakar B. ALIYU; Dauda GARBA (FUDMA Journal of Engineering and Technology, 2026)
The rapid growth of the oil mill industry has led to the generation of large volumes of oily wastewater containing high concentrations of oil, grease, suspended solids, and organic pollutants. The discharge of such effluents without adequate treatment poses serious environmental and public health risks. Conventional treatment technologies often suffer from high operational costs, complex process configurations, and limited efficiency when handling emulsified oils and high organic loads. In this context, membrane-based separation has emerged as a promising alternative due to its high removal efficiency, compact design, and potential for water reuse. Among available membrane materials, clay-based ceramic membranes have attracted increasing attention as low-cost, sustainable, and robust alternatives to polymeric and advanced oxide-based ceramic membranes. This review critically examines recent developments in the fabrication, characterization, and application of clay-based ceramic membranes for treating oily wastewater. Emphasis is placed on the selection of raw materials, fabrication techniques, sintering parameters, and key performance indicators, including permeate flux, rejection efficiency, mechanical strength, and fouling resistance. A comparative analysis with polymeric and conventional ceramic membranes is presented to highlight the advantages and limitations of clay-based systems. Current challenges related to fouling, raw material variability, energy-intensive fabrication, and scale-up are discussed, and future research directions are proposed. Overall, clay-based ceramic membranes represent a promising and economically viable solution for treating oily wastewater, particularly in resource-limited regions.
Keywords: Clay-based ceramic membranes, oily wastewater, membrane fabrication, fouling resistance, sustainable water treatment.